The effect of mobile marketing on the purchase of staple products: a case of bottom of the pyramid consumers in Khayelitsha - Mvula, Wandile (School of Management Studies, 2020)
The growth of mobile penetration in Africa has seen a rise in marketers seeking new ways of using mobile marketing to improve their business and develop sustainable marketing strategies. An empirical study on BOP consumers living in Khayelitsha, Cape Town, comprising a survey of a sample of 385 respondents, was conducted. The measurement items were assessed through six hypotheses using Structural Equation Modelling with Smart PLS 3 software. The results confirm that there is a significant relationship between social influence and trust, price sensitivity and purchase intention, service quality and trust and lastly, between service quality and satisfaction. The relationship between trust and purchase intention and the relationship between satisfaction and purchase intention are not significant. The relationship between service quality and satisfaction showed the strongest significance amongst the hypotheses, whereas the weakest relationship showing the least significance effect amongst the hypotheses is between satisfaction and purchase intention. Implications of the study suggest that managers should consider the BOP consumer differently when marketing to them as they have different consumer behaviours to other market segments. For future research, more research should be done on the BOP with regard to their adaptions to mobile marketing as this will help marketers to find better marketing strategies for their businesses to better serve this market segment. Recommendations and limitations on mobile marketing adoption within BOP are discussed.